Differential associations of mental health, mild traumatic brain injury and substance use between male and female university students - Alyssia Wilson; Jared Cherry; Kristina Gicas; Magdalena Wojtowicz (PLoS ONE, 2026)
Background More severe substance use, defined as higher scores on validated measures of problematic use, is increasing within young adult populations. Substance use has been associated with mild traumatic brain injury (mTBI) and elevated symptoms of depression and anxiety. We aimed to understand the relationship between these factors and sex differences in a university sample. Method 894 university students (372 males and 522 females, aged 18–25 years) self-reported their mTBI history, substance use (Alcohol Use Disorders Identification Test (AUDIT) and the Cannabis Use Disorders Identification Test-Revised (CUDIT-R)), and psychological measures (Patient Health Questionnaire–9 (PHQ-9) and Generalized Anxiety Disorder–7 (GAD-7). Regression analyses examined whether the number of previous mTBIs was associated with increased cannabis (within the past six months) or alcohol use (within the past twelve months) severity. Logistic and linear regression models were used to explore how mTBI history, sex, and mental health symptoms relate to the likelihood and severity of cannabis and alcohol use and were also run separately by sex. Results Individuals with multiple mTBIs reported more problematic substance use and a higher number of substances used. Hazardous substance use, as defined by scores above AUDIT and CUDIT-R cut-offs, was associated with both a previous history of mTBI and greater scores on depression and anxiety measures. Individuals with higher scores on an anxiety measure were more likely to use cannabis, especially if they had a history of mTBI. A history of mTBIs and higher current depression scores among cannabis users was associated with more problematic cannabis use. Among alcohol-using individuals, those with higher depression scores in addition to a history of mTBI were more likely to endorse more problematic alcohol use. Finally, males and females were affected differently by mental health and mTBI risk factors. Conclusion mTBI history and mental health problems may be associated with hazardous substance use, but these findings highlight the importance of considering sex-specific risk patterns when developing interventions or preventive strategies for young adults with a history of mTBI or elevated anxiety/depression symptoms.